2016
DOI: 10.1080/00071668.2016.1214682
|View full text |Cite
|
Sign up to set email alerts
|

The effect of volatile oil mixtures on the performance and ilio-caecal microflora of broiler chickens

Abstract: The aim of this study was to investigate the individual and combined effects of rosemary, oregano and fennel volatile oil (FVO) supplementation on the performance and ilio-caecal bacteriological flora of broiler chickens. A total of 800 male Ross-308 broiler chickens were divided equally into 8 groups; each contained 100 chickens. The study included a control treatment (NC) with no dietary additives that was supplemented with oils according to the following 7 treatments: 200 mg α-tocopherol acetate/kg (PC), 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
6
18
0
Order By: Relevance
“…Several in vivo studies indicated that essential oils increased the Lactobacillus group and decreased E. coli or total coliforms in piglets ( Namkung et al., 2004 , Castillo et al., 2006 , Li et al., 2012 , Zeng et al., 2015 , Wei et al., 2017 ). These results were consistent with the results observed in several poultry studies with the supplementation of essential oils ( Oviedo-Rondón et al., 2006 , Tiihonen et al., 2010 , Amerah et al., 2011 , Basmacioglu-Malayoglu et al., 2016 , Cetin et al., 2016 , Liu et al., 2017 ), suggesting that essential oil treatment led to some fundamental changes within gut microbiota mainly in the number of observed Lactobacillus species. However, studying the effects of essential oils on the gut microbiome of pigs with integrated approaches (e.g., various molecular and “omics” technologies as well as bioinformatics and statistical analyses) is still needed in order to comprehensively monitor the shifts in composition and functionality of the microbiota in response to dietary essential oils treatments.…”
Section: Effect Of Essential Oils On Intestinal Microbiota and Microbsupporting
confidence: 91%
“…Several in vivo studies indicated that essential oils increased the Lactobacillus group and decreased E. coli or total coliforms in piglets ( Namkung et al., 2004 , Castillo et al., 2006 , Li et al., 2012 , Zeng et al., 2015 , Wei et al., 2017 ). These results were consistent with the results observed in several poultry studies with the supplementation of essential oils ( Oviedo-Rondón et al., 2006 , Tiihonen et al., 2010 , Amerah et al., 2011 , Basmacioglu-Malayoglu et al., 2016 , Cetin et al., 2016 , Liu et al., 2017 ), suggesting that essential oil treatment led to some fundamental changes within gut microbiota mainly in the number of observed Lactobacillus species. However, studying the effects of essential oils on the gut microbiome of pigs with integrated approaches (e.g., various molecular and “omics” technologies as well as bioinformatics and statistical analyses) is still needed in order to comprehensively monitor the shifts in composition and functionality of the microbiota in response to dietary essential oils treatments.…”
Section: Effect Of Essential Oils On Intestinal Microbiota and Microbsupporting
confidence: 91%
“…One interesting point is the effect of EOs in gastrointestinal microbiota composition, where supplementation with them has been shown to exert a positive effect—decreasing the pathogenic microorganism while increasing the number of probiotic bacteria such as Lactobacillus spp. [96,97,98]. Correspondingly, in weaned piglets, EOs or their main active compounds positively modulated gastrointestinal microbiota [23,99,100].…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with different levels of RO (0.015% or 0.030% of the diet) or a combination of RO with OO (both at 0.0075% and 0.0150% of the diet, respectively) during a 42 day trial did not affect broilers’ FI compared with VitE (200 mg/kg) [ 24 ]. In addition, no significant variations in FI were reported when broilers were supplemented for 42 days with OO, RO, or fennel volatile oil (FVO) (each at 0.01% of the diet) or with a mixture of them (VOM, 0.01 to 0.4%) [ 25 ]. Moreover, olive leaf extract (OLE) dietary supplementation (0.2% and 0.4% of the diet) did not affect FI in broilers reared under heat stress (HS) during a 14 day period compared with control and VitE treatments [ 26 ].…”
Section: Potential Plant Extracts and Plant By-products As Alternative Sources Of Vitamins For Poultry Feedingmentioning
confidence: 99%